2020
DOI: 10.3390/agriculture10070256
|View full text |Cite
|
Sign up to set email alerts
|

Prospects of Improving Agricultural and Water Productivity through Unmanned Aerial Vehicles

Abstract: Unmanned Aerial Vehicles (UAVs) are an alternative to costly and time-consuming traditional methods to improve agricultural water management and crop productivity through the acquisition, processing, and analyses of high-resolution spatial and temporal crop data at field scale. UAVs mounted with multispectral and thermal cameras facilitate the monitoring of crops throughout the crop growing cycle, allowing for timely detection and intervention in case of any anomalies. The use of UAVs in smallholder ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
50
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 99 publications
0
50
0
3
Order By: Relevance
“…In 2016, IWMI further developed an improved irrigated area map for Asia and Africa using canonical correlation analysis and time-lagged regression at 250 m spatial resolution for 2000 and 2010 [13]. Although these datasets are important for indicating irrigated areas, they generally over-estimate the areas due to the low spatial resolution data used [18]. A recent study in South Africa has shown how low spatial resolution data can result in over-estimates of irrigated areas, particularly in smallholder fields that are about 2 ha in size, very small to be detected by low spatial resolution satellites [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2016, IWMI further developed an improved irrigated area map for Asia and Africa using canonical correlation analysis and time-lagged regression at 250 m spatial resolution for 2000 and 2010 [13]. Although these datasets are important for indicating irrigated areas, they generally over-estimate the areas due to the low spatial resolution data used [18]. A recent study in South Africa has shown how low spatial resolution data can result in over-estimates of irrigated areas, particularly in smallholder fields that are about 2 ha in size, very small to be detected by low spatial resolution satellites [18].…”
Section: Introductionmentioning
confidence: 99%
“…Advances in remote sensing technologies in conjunction with the emergence of big data and cloud-based processing platforms such as Google Earth Engine (GEE) are facilitating the classification of irrigated areas within improved accuracies in a time and costeffective manner, enhancing the monitoring of these at both local and global scales [19,20]. This is aided by freely available high-resolution remotely sensed products and novel non-parametric machine learning algorithms for land use classification [18,21,22]. Supervised image classification machine learning algorithms include Support Vector Machine (SVM), Random Forest (RF), decision tree algorithms, and Extreme Gradient Boosting (XGboost) [23].…”
Section: Introductionmentioning
confidence: 99%
“…Today, varieties of UAVs, characterised by different flight mechanics and take-off weights, and equipable sensors are continuously put on the market, providing a wide choice for operators in the sector even at minimal costs [5]. On the other hand, their versatility and transversality have triggered new application areas [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…This development holds promise for the hot and dry climates and water scarce regions such as Southern Africa. Remote sensing, and particularly the of use unmanned aerial vehicles (UAVs), also called drones, has become an important components of agricultural water management, particularly in irrigation scheduling for both commercial and smallholder sub-sectors [56]. Developments in precision farming have been aided by freely available remotely sensed products and high and user-defined spatial and temporal resolution drone images.…”
Section: Adaptation Options and Achieving Sustainable Development Outmentioning
confidence: 99%
“…UAVs can precisely estimate crop loss by comparing the pre-and post-disaster images [59]. This pre-and post-crop damage data is critical for insurance companies as it provides information that allows assessment of the damage incurred by farmers [56]. This is particularly relevant as insurance companies move towards insuring smallholder farmers against extreme weather events [60,61].…”
Section: Adaptation Options and Achieving Sustainable Development Outmentioning
confidence: 99%